2016
DOI: 10.15414/afz.2016.19.01.11-14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humic substances on the production parameters of pheasant hens

Abstract: There were observed the effects of administration of humic substances on health, feed conversion, production parameters, egg quality and hatchability of pheasants. The supplement of humic substances at the concentration 0.5 % in the feed mixture significantly influenced the hatchability percentage of pheasant chicks. The hatchability 72.9 % was achieved in the group without addition of humic substances. On the contrary, the hatchability 83.4 % was achieved in the experimental group in the case of addition of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Experiments on the application of HS in animal rations have mainly focused on monogastric animals. The positive effects of humates on the growth of broiler chickens, productivity and health of laying poultry, as well as the chemical composition of eggs have been demonstrated in several studies (Trziszka et al, 2011;Mirnawati and Marlida, 2013;Sopoliga et al, 2016 ). The results of Wang et al (2020) indicated that humic acids in the rations improved growth performance and health of piglets.…”
Section: Introductionmentioning
confidence: 89%
“…Experiments on the application of HS in animal rations have mainly focused on monogastric animals. The positive effects of humates on the growth of broiler chickens, productivity and health of laying poultry, as well as the chemical composition of eggs have been demonstrated in several studies (Trziszka et al, 2011;Mirnawati and Marlida, 2013;Sopoliga et al, 2016 ). The results of Wang et al (2020) indicated that humic acids in the rations improved growth performance and health of piglets.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, HS with supplementation with probiotic products based on lactobacilli significantly increased the egg albumen index and Haugh units. Sopoliga et al [25] reported increased hatchability in pheasant laying hens after the intake of humic substances in comparison to hens fed with the conventional feed mixture.…”
Section: Introductionmentioning
confidence: 99%